Experimental And Numerical Investigation Of Rotor-Rotor Dynamic Interactions In A Tilting Multirotor System - Sharma, T.; Titurus, B.; Rezgui, D. (My University, 2025)
This study aims to study rotor-rotor dynamic interactions in a tilting multirotor test rig through a combined experimental and numerical investigation. The rig was dynamically scaled to simulate the ordering and relative spacing of leading structural modes observed in NASA's X-57 DEP wing. An experimental modal analysis was performed under stationary and rotational conditions with shaker excitation, and the results were compared to a beam element based model simulated in MSC NASTRAN. The gyroscopic effects arising from propeller spin were introduced in the model using the Rotordynamics toolbox in MSC NASTRAN. The model was able to accurately represent the baseline structural dynamic response to within ±5% of experimental values and also captured key dynamic features such as mode frequency divergence, whirling and veering across the investigated rotor speed range. The dual rotor configuration, in contrast to the single rotor case, exhibited additional mode divergence, several distinct overlapping veering regions, and switching of mode shape properties. These results show that the coupled dual rotor configuration produces rich interaction-driven modal phenomena that transcend those encountered in isolated cases. The validated modelling method provides a basis for identifying such regimes and examining the effect of rotor spacing on the emergence and development of interaction-driven behaviour in multirotor systems.